وسائل التواصل الاجتماعي مساعدةً لتعلّم اللغة (SMALL) في تعليم اللغة العربية - Maesaroh, Miftakhul (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2019)
Nowaday, more educators are using social media as an educational tool. Many researchers have argued that social media are appropriate for supporting students active learning especially in second language learning. Arabic as one of the world’s languages is second language or foreign language in Indonesia. Arabic language Is increasingly reaching various countries marked by the increase of speakers from this language. The purpose of this study is to shed some light of using social media toward Arabic learning for Arabic as a foreign languages (AFL) students. The method used is descriptive method by examining several references from books, educational journals, and previous studies. With the results of this research that some social media such as Facebook, Instagram, and YouTube can be used as media in learning Arabic that includes four istima’, kalam, qiroah, and kitabah language skills by adjusting the features of each social media.